The Role of the Ministry of Lector and Acolyte in the Context of the Instruction for Parishes in the Service of Evangelisation (June 29, 2020) and the Letter Spiritus Domini (January 10, 2021) - Biela, Bogdan (Verbum vitae, 2024)
The principal weight of the Church’s responsibility for evangelization rests on the parish. However, the pastoral practice shows that there is no sufficient principle to organize the missionary life of the parish as a community of communities. This frequently leads to confusion in a multitude of activities, which contributes to the failure of the parish to fulfill its principal evangelizing mission. Firstly, the article shows how the introduction of ministries of lector and acolyte into the life of the parish may help revitalize the basic functions of the parish, which are: martyrdom, liturgy, and diakonia. Men and women who discovered their specific vocation to the ministry of lector and acolyte may become pillars of concrete parish groups and apostolic work realized in the parish. It is closely related to a proper understanding of the ecclesial dimension of each of these ministries. In view of the above, the article presents pastoral inspirations of the Instruction of the Congregation for the Clergy The Pastoral Conversion of the Parish Community in the Service of the Evangelising Mission of the Church, and the indications of Pope Francis’ Apostolic Letter Spiritus Domini. Secondly, the text presents the liturgical ministries in the light of the hierarchical, charismatic, and spousal dimension of the mystery of the Church. The final part of the article describes the pastoral dimension of these ministries in realizing the evangelizing mission of the Church.Pope Francis' apostolic letter Spiritus Domini, regarding the access of women to the ministries of lector and acolyte (10.01.2021), is a call to consider the role of these ministries in realizing the building of the parish community of communities. This call is, in turn, expressed in the Instruction of the Congregation for the Clergy The pastoral conversion of the Parish community in the service of the evangelising mission of the Church (29.06.2020). The article shows that introducing the established ministries of lector and acolyte into the life of the Church can help revitalize the basic parish functions, which are: martyrdom, leiturgy and diakonia. To appoint someone for service in the community is to make them a pillar on which the concrete apostolic work realized in the parish can rest. It reaches its peak and expresses itself most fully in the liturgy and extends to all areas of the life of the parish community. Accordingly, the permanent establishment of lay men and women for the ministry of lector and acolyte should be based on the discernment of a God-given vocation. Adequate preparation should include not only liturgical matters but also the ability to undertake a specific mission in the parish community. The aim shall be achieved when the ecclesial dimension of each of these ministries is properly understood.